Host cell type-dependent translocation and PhoP-mediated positive regulation of the effector SseK1 of Salmonella enterica - Baisón-Olmo, Fernando; Galindo-Moreno, María; Ramos-Morales, Francisco (Frontiers in Microbiology, 2015)
Salmonella enterica expresses two virulence-related type III secretion systems (T3SSs) encoded in Salmonella pathogenicity island 1 (SPI1) and SPI2, respectively. SseK1 is a poorly characterized substrate of the SPI2-encoded T3SS. Here, we show that this effector is essential to get full virulence both in oral and intraperitoneal mice infections, in spite of not having a role in invasion or intracellular proliferation in cultured mammalian cells. In vitro, expression of sseK1 was higher in media mimicking intracellular conditions, when SPI2 was induced, but it was also significant under SPI1 inducing conditions. A detailed analysis of translocation of SseK1 into host cells unveiled that it was a substrate of both, T3SS1 and T3SS2, although with different patterns and kinetics depending on the specific host cell type (epithelial, macrophages or fibroblasts). The regulation of the expression of sseK1 was examined using lacZ and bioluminescent lux fusions. The two-component system PhoQ/PhoP is a positive regulator of this gene. A combination of sequence analysis, directed mutagenesis and electrophoretic mobility shift assays showed that phosphorylated PhoP binds directly to the promoter region of sseK1 and revealed a PhoP binding site located upstream of the predicted -35 hexamer of this promoter.